Transitivity Analysis on Framing in the Online News Articles - Agustinus Dias Suparto (Ranah: Jurnal Kajian Bahasa, 2018)
News is the way to let public know about certain occurrences around the world. In Indonesia, the case of Ahok which has been sentenced for two years has been an international phenomenon. There are two factions which are opposite two each other about the case. Thus, report which can be found in the news may have different perspectives, depending on the writers’ views. There are bias and framing which leads people on the writer’s perspective. This paper will try to analyze two news articles on Basuki Tjahaja Purnama’scase which are taken from antaranews.com and hrw.org using Systemic Functional Linguistics (SFL). The data will be examined using transitivity analysis which can reveal the different perspectives of these two news articles by breaking down the sentences which shows the participants, process and circumstances involved. At the end of this paper, it shows how the difference in using of participants, process and circumstances creates different perspectives of the writer.  AbstrakBerita merupakan alat pemberitaan kepada masyarakat luas tentang peristiwa yang terjadi di dunia. Di Indonesia, pemberitaan tentang Ahok yang telah didakwa dua tahun penjara telah menjadi perbincangan dunia. Dalam menyikapi pemberitaan ini, terdapat dua kelompok besar yang saling berlawanan sehingga memungkinkan terdapat perbedaan laporan dalam berbagai pemberitaan. Maka, terjadi ketaksesuaian informasi dan framing yang berujung pada perbedaan pandangan tentang objek pemberitaan. Artikel ini membahas tentang pemberitaan Basuki Tjahaja Purnama di dua berita online, yaitu antaranews.com dan hrw.org menggunakan analisis ketransitifan dalam Systemic Functional Linguistics(SFL) yang dipopulerkan oleh Halliday. Data dibahas secara rinci dengan menganalisis aspek-aspek ketransitifan pada setiap kalimat dalam berita. Pada akhirnya, artikel ini mengungkap bagaimana penggunaan partisipan (participants), proses (process) dan situasi (circumstances) dalam kalimat dapat memengaruhi sudut pandang dari penulis berita